Entrepreneur capacities and effective personality in students of a private university of Lima - Torres Valladares, Manuel (2013)
One of the biggest problems that our country faces is that in the university world, young people are trained to be employees and not to be entrepreneurs, to recieve orders and not to give them, to use tools and techniques already created and not to create or recreate them. This has lead into a social reality in which inventiviness and creativity are not incetivated nor rewarded, the quick solving of problems is not appreciated and much less, innovative managament. For this reason, the main purpose of the current investigation consists in having a description of the characteristics of the students’ effective personality and how these relate to their entrepreneur capactities. In the development of the current investigation were used the Effective Personality Inventory of Del Buey and the Entrepreneur Capacities Inventory of Moriano, J. The statistical analyses the tests were submitted to indicate us the instruments are valid and reliable. These tests were applied to 155 students of the Administration Faculty of a private university of Lima. The statistical results indicate us that the effective personality of the students is related to their entrepreneur capacities. Moreover, it was found that the students present significant differences regarding to their academic cycle in the variable of effective personality.